A critical investigation of selected Cape and Transkei environment study programmes in junior primary schools - Vinjwa, Nobuzwe (Rhodes University, Faculty of Education, Department of Education, 1993)
The introduction of Environment Study (ES) into the Junior Primary (JP) phase of the school was to facilitate the young learners' development of a sense of place, time and social identity. ES is important in the JP phase because it introduces pupils to the world around them and the environmental issues that affect their lives. ES in the JP phase can also provide pupils with the basic knowledge for survival in a changing world. ES in the JP phase is primarily designed to aid the pupils' development of a sense of identity. As with geography, it is concerned with space, place and time; and these are the criteria that should be taken into consideration in developing the child's sense of identity. Implementation of ES is largely influenced by the expertise and experience of the teachers, which will, in turn, influence their interpretation of the ES syllabus. The goals of ES require teachers to be able to use a variety of teaching strategies and to develop and use a variety of teaching resources. This study investigates existing ES programmes in a number of selected schools in the Cape, DET and Transkei in order to establish the extent to which pupils' developing sense of time, place and social identity are taken into consideration. Observations and interviews were conducted to assess the current ES syllabi for the Cape, DET and Transkei schools in relation to Catling's (1987) criteria; and to evaluate existing ES programmes in the six selected schools in the Grahamstown, Umtata and Mqanduli districts to ascertain the extent to which they met Catling's criteria. The results reveal that in all the Education Departments' syllabi, pupils' needs to developing a sense of time, place and social identity, as suggested by Catling's (1987) criteria, were considered only to a limited extent. Even in the syllabi where these were developed, it was by mere coincidence. Secondly, the programmes in the different schools observed did not meet Catling's criteria sufficiently, because the teachers were ignorant of Catling's criteria. Conclusions are drawn and recommendations made for teachers' awareness of Catling's criteria to be promoted, so that teachers can apply these in their teaching of ES; and for both Cape and Transkei ES programmes in the JP phase to be revised.
Keywords: Environmental education -- Study and teaching (Elementary) -- South Africa; Environmental education -- South Africa